Death Anxiety and Its Predictors Among Older Adults - Zahra Zahedi Bidgol; Zahra Tagharrobi; Zahra Sooki; Khadijeh Sharifi (Guilan University of Medical Sciences, 2020)
Introduction: Death anxiety can negatively affect recovery among older patients. Objective: study aimed to assess death anxiety and its predictors among older adults during and after hospitalization. Materials and Methods: This cross-sectional study was conducted in 2017 on 241 hospitalized patients aged ≥60 years. The study subjects were consecutively recruited from a hospital in Kashan City, Iran. The required data were collected in the first and the third hospitalization days (T1 and T2) and the seventh day after hospital discharge (T3) using the Mini-Mental State Examination, a Death Anxiety Contributing Factors questionnaire, the Templer Death Anxiety Scale, the Life Satisfaction Index-Z Scale, and the Spiritual Well-Being Scale. For the statistical evaluation, repeated measures Analysis of Variance (ANOVA), the stepwise multiple linear regression, and the rank regression analyses were used. Results: The Mean±SD score of death anxiety at T1-T3 was 6.74±3.81, 7.38±3.64, and 6.18±3.60, respectively. Death anxiety at T2 was significantly greater than T1 and T3 (P=0.0001). Approximately 17.7% of the total variance of death anxiety at T1 was explained by the number of hospitalizations, satisfaction with hospital staff's performance, and spiritual well-being. The significant predictors of death anxiety at T2 were marital status, satisfaction with hospital staff's performance, children's gender, satisfaction with bed arrangement, age, and the number of hospitalizations, which explained 32.1% of the total variance. Moreover, 15.4% of the variance at T3 was explained by satisfaction with bed arrangement and receiving education at hospital discharge. Conclusion: Older adults suffer from moderate death anxiety during and after their hospitalization due to various factors. Managing death anxiety contributing factors is necessary to alleviate it among older adults